(untitled) (Research, Society and Development, 2020)
The present study aims to understand the epidemiological profile of premature newborns admitted to a Neonatal Intensive Care Unit (NICU). This is a research with a quantitative approach, cross-sectional design and descriptive character that was carried out based on documentary analysis, which assesses 155 medical records of the RNPT (Premature Newborn), admitted between January 1 and December 31, 2017 in a NICU. The data were entered and stored in an Excel plan and analyzed using descriptive and inferential statistics, used in the SPSS Software version 20.0. The most prevalent age group of the parents was between 20 and 34 years old (67.1%). As for the complications evidenced during the current pregnancy, as the most frequent complications were urinary tract infection (46.5%) and hypertension (45.8%). The average birth weight found was 1744.1g. It does not refer to the length of stay, it was found that the average length of stay was 37.4. Among the most prevalent reasons responsible for hospitalization, it should be noted that (41.9%) were children with low birth weight and (30.3%) respiratory distress syndrome. Of the variables investigated, only a single marital situation can be seen that is statistically significant with a variable dependent on the degree of prematurity (p = 0.049). It is hoped that this study can contribute to new research regarding the importance of knowing the epidemiological profile of premature newborns according to the degree of its prematurity.